Hubungan Antara Bermain Game Online dengan Motivasi Belajar pada Mahasiswa - Irgi Ahmad Fahrezi; Wigyo Susanto; Dwi Heppy Rochmawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid advancement of digital technology has intensified online gaming engagement among university students and raised concerns regarding its potential effects on psychological health and learning motivation. This study aimed to examine the relationship between online gaming and students’ learning motivation. A quantitative correlational design with a cross-sectional approach was employed involving 105 students from the Faculty of Nursing, Sultan Agung Islamic University Semarang, selected through probability random sampling. Data were collected using validated and reliable questionnaires measuring online gaming intensity and learning motivation. Statistical analyses included univariate and bivariate procedures using Somers’ d test. The findings revealed that most respondents demonstrated high gaming intensity (45.7%) and low learning motivation (44.8%). The Somers’ d test produced a coefficient of –0.713 with p = 0.000, indicating a strong and significant negative relationship between online gaming and learning motivation. These results suggest that excessive gaming is associated with reduced academic focus, poorer time management, and diminished learning responsibility. The study underscores the importance of managing students’ digital behavior through healthy technology literacy and preventive academic interventions to sustain learning motivation in the digital era.